Proceedings of the 12th International Conference on Kinanthropology 2020
DOI: 10.5817/cz.muni.p210-9631-2020-31
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Age Effect in the Top 100 ATP Tennis Players 2016–2018

Abstract: The issue of the Relative Age Effect (RAE) has been monitored in the field of sports for more than 30 years. Its theoretical framework is based on the premise that during the pubescent period athletes born at the beginning of the year experience earlier biological acceleration re-sulting in a higher level of physiological, mental, morphological and psychological attributes than their later-born peers. A number of publications show that this temporary advantage often manifests itself in elite competitions at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The results of RAE research among senior elite athletes have often been varied; Savassifigueiredo et al (2020) showed a significant RAE (ES was trivial) for both sexes among elite beach handball athletes, Edgar and O'Donoghue (2005) in female and male elite senior tennis players (ES was small), Nykodým et al (2020) in elite senior ice hockey players (ES was small)), Bozděch et al (2020) in elite tennis players -Top 100 ATP 2016-2018 (ES was small).In contrast, no significant RAE (ES was medium) was found among professional Spanish footballers/soccer players (Gil et al, 2019) and also among male and female elite ski jumpers (ES was trivial) between the first and second semester (Hammer, 2020). Parma and Penna (2018) did not prove any RAE among women's elite volleyball players in Brazil (ES trivial), but they proved it among male athletes (ES medium); thus, similarly as in our study, a stronger impact of RAE was demonstrated in men.…”
Section: Discussionmentioning
confidence: 99%
“…The results of RAE research among senior elite athletes have often been varied; Savassifigueiredo et al (2020) showed a significant RAE (ES was trivial) for both sexes among elite beach handball athletes, Edgar and O'Donoghue (2005) in female and male elite senior tennis players (ES was small), Nykodým et al (2020) in elite senior ice hockey players (ES was small)), Bozděch et al (2020) in elite tennis players -Top 100 ATP 2016-2018 (ES was small).In contrast, no significant RAE (ES was medium) was found among professional Spanish footballers/soccer players (Gil et al, 2019) and also among male and female elite ski jumpers (ES was trivial) between the first and second semester (Hammer, 2020). Parma and Penna (2018) did not prove any RAE among women's elite volleyball players in Brazil (ES trivial), but they proved it among male athletes (ES medium); thus, similarly as in our study, a stronger impact of RAE was demonstrated in men.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study demonstrate that the majority of male professional tennis players that ranked among the best 100 tennis players in the ATP Rankings in the years 2016-2018 were born in Q 2 , though this finding is not in agreement with the results of studies concerning the influence of RAE in junior categories. The majority of these studies found a predominance of players born in Q 1 with a falling trend of the frequency of players born in the individual quarters up to Q 4 (Agricola et al, 2017;Bozděch et al, 2017;Koloničný et al, 2018;Ulbricht et al, 2015). As an example, we give the results of Bozděch et al (2017) who studied the influence of RAE at the World Junior Tennis Finals (WJTF, male, n=240) in the years 2012-2016.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies found a predominance of players born in Q 1 with a falling trend of the frequency of players born in the individual quarters up to Q 4 (Agricola et al, 2017;Bozděch et al, 2017;Koloničný et al, 2018;Ulbricht et al, 2015). As an example, we give the results of Bozděch et al (2017) who studied the influence of RAE at the World Junior Tennis Finals (WJTF, male, n=240) in the years 2012-2016. The authors demonstrated the influence of RAE on the basis of assessment of the statistical significance of c 2 values in individual years and throughout the whole period (p < .01).…”
Section: Discussionmentioning
confidence: 99%